Ерготерапія спортсменок старших вікових груп, які спеціалізуються в спортивних видах боротьби після лікування травм колінних суглобів - Сіренко, P. P.; Золочевський, В. В.; Ванюк, Дар'я Валеріївна; Шевченко, О. С.; Чайка, О. І.; Партика, С. С.; Sirenko, R. R.; Zolochevskyi, V. V.; Vaniuk, D. V.; Shevchenko, O. S.; Chaika, O. I.; Partyka, S. S. (My University, 2024)
У статті розглянуто актуальні питання організації системи ерготерапії спортсменок старших вікових груп, які спеціалізуються в спортивних видах боротьби, після лікування травм колінних суглобів. В процесі дослідно- аналітичної роботи проаналізовано актуальні методики ерготерапії, які забезпечують відновлення функціональних можливостей нижніх кінцівок та профілактику повторних ушкоджень у представниць досліджуваної категорії. Крім цього, членами науково-дослідної групи розглянуто фізичні, психоемоційні та когнітивні аспекти, що впливають на процес відновлення, а також запропоновано інтеграцію індивідуалізованих програм ерготерапії з метою прискорення адаптації спортсменок до змагальної діяльності. Методи дослідження: аналіз і синтез, індукція і дедукція, абстрагування, моделювання, гіпотетико- дедуктивний метод, системний підхід, метод аналогій, формалізація, контент-аналіз, метод історичного аналізу. В результаті теоретичного дослідження членами науково-дослідної групи розроблено експериментальну програму ерготерапії спортсменок старших вікових груп (ветеранок), які спеціалізуються в боротьбі самбо на етапі відновлення після лікування травм колінних суглобів. Результати дослідження впроваджені в систему ерготерапії спортсменок-ветеранок, які спеціалізуються в спортивних видах боротьби, представниць збірних команд: Запорізької, Київської, Львівської та Харківської областей України. The Article deals with topical issues of the organization of the Occupational Therapy System of Female Athletes of older age Groups who Specialize in Wrestling Sports after treatment of knee joint injuries. In the process of Research and Analytical work, current Methods of Occupational Therapy were analyzed, which ensure the restoration of the Functional capabilities of the lower limbs and the prevention of repeated injuries in the representatives of the Studied Category. In addition, the Members of the Research Group considered the Physical, Psycho-Emotional and Cognitive Aspects that affect the Recovery Process, and also proposed the integration of individualized Occupational Therapy Programs in order to accelerate the adaptation of sportswomen to competitive activities. Researchers paid attention to the use of Modern Rehabilitation Technologies, such as Kinesiotherapy, Adaptive Physical Exercises and Mental Training Methods, which allow to improve Coordination, Strength and stability of the knee joints. Research methods: Analysis and Synthesis, Induction and Deduction, Abstraction, Modeling, Hypothetical-Deductive Method, systematic approach, Method of Analogies, Formalization, Content Analysis, Method of Historical Analysis. In the process of Research and Analytical work, the personal experience of organizing the Occupational Therapy System of Sportsmen and Sportswomen of older age Groups who specialize in sports of wrestling was also used. As a Result of a Theoretical Study, Members of the Research Group developed an Experimental Occupational Therapy Program for Female Athletes of older age Groups (veterans) who Specialize in Sambo Wrestling at the Stage of Recovery after treatment of knee joint injuries.
Ergotherapy of Female Athletes of older age Groups who Specialize in Wrestling Sports after treatment of knee joint injuries
Keywords: багаторічна підготовка; боротьба самбо; бойові мистецтва; відновлення; ерготерапія; етапи; колінні суглоби; одноборства; попередження травматизму; спортсменки; multi-year training; Sambo Wrestling; Martial Arts; recovery; Occupational Therapy; stages; knee joints; Single Combat; injury prevention; Female Athletes